San Antonio Water System, Texas Carrizo Aquifer Storage Recovery Program. Issue 5 (11th August 2022) - Snyder, Grant L.; Pyne, R. David G.; Morrison, Kevin; Nixon, Kirk
Abstract: San Antonio Water System (SAWS) developed its Aquifer Storage Recovery (ASR) program in the Carrizo aquifer to provide potable water supply reliability for San Antonio during droughts while protecting natural ecosystems and threatened and endangered species at Comal Springs and San Marcos Springs and augmenting downstream flows in the San Antonio River and estuarine ecosystems. It enables SAWS to completely optimize use of its Edwards Aquifer Withdrawal Permit with no wasted water, leveling out seasonal demand stresses on the Edwards aquifer. The SAWS Carrizo ASR wellfield recovery hydraulic capacity was designed to provide 64 million gallons per day (MGD) (0.24 Mm 3 /D). However, as built, the briefly tested recovery capacity, in practice, is approximately 80 MGD (Kirk Nixon and Kevin Morrison, verbal communication, 2022). Almost 200, 000 acre feet (AF) (247 Mm 3 ) of drinking water have been stored to date. The water recovered from storage requires only re‐disinfection prior to transmission and distribution to customers. During the period 2011 to 2014, a drought of near record intensity required SAWS to recover a total volume exceeding 50, 000 AF (61.7 Mm 3 ) over the 4‐year period. The ASR wellfield area and H2Oaks treatment facility serve as a central location for integration of two other long‐term water supply strategies including desalination of brackish groundwater from the underlying Wilcox aquifer and groundwater production from the local Carrizo aquifer. Several lessons have been learned during 18 years of ASR operation, as addressed in this article. Abstract : Article impact statement : Lessons learned from 18 years' operating experience at a large ASR wellfield for San Antonio Water System (SAWS), Texas.